Penilaian Instalasi Pengolahan Lumpur Tinja (IPLT) di beberapa kota di Indonesia dengan menggunakan analisa faktor - Fitrijani Anggraini; Reni Nuraeni (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
The problem of water pollution is complex. There are many factors that influence the successfull of efforts for water pollution control. The construction and operation of septage treatment facility (IPLT) is an efforts for controlling pollution from domestic activities. The successfull of IPLT management cannot be assessed from physical aspect of the building only. Other aspects such as quality of effluent, sludge supply, idle capacity, the rate of surface loading and volumetric loading, human resources, organization, standard operating procedures (SOP), the tariff and others should be consider for decision making to manage IPLT better. The purpose of this study is to describe the application of factor analysis method to solve a complex problem of IPLT through identifying the main causes and formulate solutions. Factor analysis is one of decision with multicriteria. The primary data research in 2014 used as reference for analyzing. The conclusion of this study is the factor analysis is able to classify 12 indicators into 3 factors without reducing the meaning of the constituent indicator, thus simplifying the decision making process. Significant factors that affecting the successfull of IPLT performance in controlling water pollution are : continuity of sludge supply, clarity of roles and responsibilities, availability, novelty, accesibility and simplicity of SOP.